The Manifestation of Teachers' Management Styles and Personal Characteristics In Pedagogical Activities - Turayeva, Dilaruz (Indonesian Journal Publisher, 2025)
This article presents the results of a study of management styles (authoritarian, democratic, liberal) and personal characteristics of teachers, their gender differences and their relationship with various psychological factors. In order to evaluate teachers' management methods and their impact on the educational process, the study concluded that teachers' personal characteristics and work experience were related to their management methods, and significant correlations were found between various factors of the Kettell personality test. The article presents an analysis of these relationships.